The Transformation of Teachers' Digital Competence in Online Learning: Analysis of Success Factors and Implementation Challenges - Muhammad Rafly Juliawan Fernandes; Suprih Widodo; Ulva Elviani; Rahmawati Salsabila (The Future of Education Journal, 2025)
This study systematically analyzes the transformation of teachers' digital competence within the context of online and blended learning. Employing a Systematic Literature Review (SLR) of 25 articles published between 2019–2024, the research identifies the underlying success factors and implementation challenges. The findings reveal that TPACK and DigCompEdu are the most dominant frameworks guiding research and development. Key success factors include high Self-Efficacy and Internal Motivation among teachers, supported by Continuous Hands-on Training and Institutional Leadership. The greatest challenges are rooted in the Infrastructure Gap (First-Order Barriers), prevalent in developing countries, and the Pedagogical Digital Skill Gap (Second-Order Barriers), which refers to teachers' inability to integrate technology for effective interaction and assessment. Successful implementation requires a shift from passive training to Learning by Design models (TPACK-based projects) and continuous Coaching to bolster teacher confidence and bridge the Pedagogical Digital Gap.